Cultura organizacional e estratégia competitiva: uma pesquisa no segmento bancário - Torretta, Ivan Luis Agnelli (2016)
This dissertation investigated the current state of the organizational culture and style of competitive strategy adopted by a large financial institution in the national financial system that operates as a conglomerate, in order to verify the existence of relationship between the two variables. The survey results confirmed the relationship hypothesis proposed in the theoretical framework used, and presented the cultural type perceived as "hierarchical", characterized by being focused on the domestic environment, enhance the stability, strong monitoring and internal control. Perceived competitive strategy was "defensive" characterized by conservatism, strong control mechanisms and low risk exposure. Cultural type perceived to be desired was the "group" characterized by enhancing the ties established by its members and the teamwork that, according to the association proposed the theoretical framework, correspond to the reactive strategy outlined in the strategy of absence of condition only with promoting strategic nature of action in cases of concrete existence of any threat from its competitors. The theoretical framework for the verification of the perceived and desired cultural type was the model of Quinn and Rohrbaugh (1983) that allows a cultural comparative study from the core values that predominate in the company. For the analysis of competitive strategy was used Miles model and Snow (2003) that typifies the competitive strategy in four configurations, according to certain corporate behaviors present in the organization. To relate the cultural typology to competitive strategy measured, it used the association proposed by Quinn and McGrath (1985) that relates these two proposals for cultural and strategic typology used in this study